2008
DOI: 10.1140/epjb/e2008-00112-3
|View full text |Cite
|
Sign up to set email alerts
|

“Illusion of control" in Time-Horizon Minority and Parrondo Games

Abstract: Please replace the paragraph immediately before equation (7) with: "Actions are drawn from a reduced strategy space (RSS) of dimension r = 2 m+1 . Each action is associated with a strategy k and a history µ(t). There are 2 m histories. Together, all actions by history and strategy (converted for convenience from {O,1}) can be represented in table form as a dim(RSS)×2 m binary matrix (i.e., a µt k ∈ {−1, 1}). In this case, the table reads:"

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…For example, it has been studied how random strategies of promotions can help to face the problems raised by the so-called Peter principle in hierarchical organizations [22][23][24] or how randomly selected legislators may improve the efficiency of a public institution like a Parliament [25]. Other groups have successfully explored the success of similar stochastic strategies also in minority and Parrondo games [26]. In this respect, it seems of particular interest the investigation of the role of random strategies in financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been studied how random strategies of promotions can help to face the problems raised by the so-called Peter principle in hierarchical organizations [22][23][24] or how randomly selected legislators may improve the efficiency of a public institution like a Parliament [25]. Other groups have successfully explored the success of similar stochastic strategies also in minority and Parrondo games [26]. In this respect, it seems of particular interest the investigation of the role of random strategies in financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when the agents only remember the last T payoffs, the whole dynamics is Markovian of order T ; simple analytical formulations give many insights about the origin of large fluctuations [84,158].…”
Section: Reduced Set Of Strategiesmentioning
confidence: 99%
“…Parrondo's paradox [12,13,14] is a counterintuitive behaviour that takes place in the context of game theory and represents one of the numerous examples of systems where noise and randomness can play a beneficial role [15,16,17,18,19,20,21,22]. In particular, Parrondo showed that two losing games can result in a winning trend when played in an alternating or in a random sequence by a single player.…”
Section: Parrondo's Paradox In Single and Collective Gamesmentioning
confidence: 99%